2016
DOI: 10.1021/acs.jpcb.6b06420
|View full text |Cite
|
Sign up to set email alerts
|

The Size of AOT Reverse Micelles

Abstract: Reverse micelles (RMs) made from water and sodium bis(2-ethylhexyl) sulfosuccinate (AOT) are commonly studied experimentally as models of aqueous microenvironments. They are small enough for individual RMs to also be studied by molecular dynamics (MD) simulation, which yields detailed insight into their structure and properties. Although RM size is determined by the water loading ratio (i.e. the molar ratio of water to AOT), experimental measurements of RM size are imprecise and inconsistent, which is problema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
67
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(87 citation statements)
references
References 57 publications
3
67
0
Order By: Relevance
“…The results were shown in Figure 2 and 3. Results showed that in the extraction process, the reaction time was linearly related to 2 3…”
Section: Effect Of Temperature On Protein Extraction Ratementioning
confidence: 99%
See 1 more Smart Citation
“…The results were shown in Figure 2 and 3. Results showed that in the extraction process, the reaction time was linearly related to 2 3…”
Section: Effect Of Temperature On Protein Extraction Ratementioning
confidence: 99%
“…Reverse micelle are agglomerates in which a surfactant is dissolved in a non-polar solvent [1,2]. In a reverse micelle solution, the hydrophobic groups of the surfactants come into contact with the solvent, and the hydrophilic groups face inward to form a polar core [3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Reverse micellar extraction (RME) has been recognized as an attractive alternative for downstream processing of biomolecules due to its simplicity, low surface tension at the interface and ease of scaling up [11]. Reverse micelles are optically transparent, self-assembled aggregates of surfactant clustered around water droplets suspended in an organic solvent [12]. The micelles are capable of solubilizing biomolecules of interest in its inner aqueous core according to their hydrophobicity, size, and charge without excessive loss of activities [13].…”
Section: ■ Introductionmentioning
confidence: 99%
“…[44][45][46] In seminal studies by Ladanyi et al, it was shown that the RM water core dynamics is dependent on distance from the surfactant head molecule and water loading, [47][48][49][50] providing an explanation of water loading dependence of water dynamics within RMs. 51,52 Eskici and Axelsen recently estimated the size distribution of AOT RMs at a water loading of 7.5 via conventional molecular dynamics (MD) simulations 53 and investigated the water exchange mechanism upon the fusion of RMs. 54 Additionally, coarse-grained simulations of RM formation have demonstrated the role of the water core in the RM formation mechanism.…”
Section: Introductionmentioning
confidence: 99%